Vegetation and climate change, fire-regime shifts and volcanic disturbance in Chiloé Continental (43°S) during the last 10, 000 years. (1st September 2015) - Henríquez, W.I.; Moreno, P.I.; Alloway, B.V.; Villarosa, G.
Abstract: Disentangling the roles of paleofires and explosive volcanism from climatic drivers of past vegetation change is a subject insufficiently addressed in the paleoecological literature. The coastal region of the Chiloé Continental sector of northwestern Patagonia is ideal in this regard considering its proximity to active eruptive centers and the possibility of establishing comparisons with more distal, upwind sites where volcanic influence is minimal. Here we present a fine-resolution pollen and macroscopic charcoal record from Lago Teo with the aim of documenting the local vegetation and climate history, and assessing the role of disturbance regimes as drivers of vegetation change during the last ∼10, 000 years. The Lago Teo record shows a conspicuous warm/dry interval between ∼7500 and 10, 000 cal yrs BP followed by a cooling trend and increase in precipitation that has persisted until the present, in agreement with previous studies in the region and interpretations of past southern westerly wind activity at multi-millennial scales. The presence of 26 tephras throughout the record allows examination of the relationship between explosive volcanism and vegetation change under contrasting climatic states of the Holocene. We found consistent statistically significant increases in Tepualia stipularis after tephra deposition over the last 10, 000 years, in Eucryphia/Caldcluvia between 7500 and 10, 000 cal yrs BP and in Hydrangea over the last 7500 years. Our results indicate a primary role of climate change as driver of long-term vegetation change and as a modulator of vegetation responses to volcanic disturbance at multidecadal and centennial timescales. Highlights: The Lago Teo record shows a warm/dry interval between ∼7500 and 10, 000 cal yrs BP. The record shows a cooling trend and increase in precipitation since ∼7500 cal yrs BP. Volcanism changed the structure/composition of the vegetation during the Holocene. The response of different opportunistic species is modulated by the climate state.